Simulasi Pengaman Pada Saluran Kabel Tegangan Tinggi Berupa Line Current Differential (LCD) Berbasis Arduino Mega 2560 Dengan Tampilan Human Machine Interface dan Notifikasi Blynk - Fakhruddin Mangkusasmito; Eko Ariyanto; Muchamad Syafruddin (Department of Electrical Engineering, UNJANI, 2021)
Power transmission protection is a system that serves as a safety in the electrical equipment of a transmission network so that the process of channeling electrical energy to the consumer can run well. The power transmission system of the generating system can be through Extra High Voltage Overhead Line, High Voltage Overhead Line, and High Voltage Underground Cable. In each transmission line is required protection system that can protect the electricity distribution process to the consumer. High voltage underground cable is a transmission system that delivers electrical energy through a cable that is buried in the ground. Although it is in the ground and protected by an excellent insulation system, but does not escape also from the occurrence of interference. In the land cable channel protection system is known as the Line Current Differential (LCD) which is a protection system that works under Kirchoff Law 1 by comparing incoming flows and exiting flows, with uptime instantaneously. This research made a simulation of such system, using Arduino Mega 2560 and be equipped with Internet of Things (IoT) monitoring using Blynk. The test result indicated that the system can work properly